PENEGAKAN HUKUM LEGALISTIK DALAM PERSPEKTIF SOSIOLOGIS - Cecep Wiharma (Jurnal Hukum Mimbar Justitia, 2017)
The law society's awareness of the factors that strongly holds an important role in the efforts of the law enforcement itself, because it is this persfektif that need to be arranged so that the rule of law in this country can run. The relevance of the rule of law in the perspective of the rule of Justice as part of the legal consciousness of the public, is an alternative effort over mistrust against law enforcement officials of the ruling is positive and which is the mainstream of the view legalistic. When talking about the law in persfektif justice in the area of ethics or morality and does not discuss the legal issues in a sense narrow. How positive law is made, and whether it has made positive law represents the community's sense of fairness, as well as the legal apparatus that this mentality of enforcing the law? The culture of the law society legal culture depends on its members which is influenced by the background of his education, the environment, culture, position, even the interests.Â Keywords: Law enforcement, Legal Awareness, and Justice